어린이 영양지수(NQ)를 이용한 광주 지역 일부 고학년 초등학생의 영양상태 평가 - 조희연; 김경윤; 윤정미; Heeyoen Jo; Kyoung Yun Kim; Jung-Mi Yun (Journal of the Korean Society of Food Culture, 2020)
This study was conducted to evaluate the overall dietary habits and nutritional status of 294 elementary school students located in Gwangju using the NUTRILITE nutrition quotient (NQ). The NQ score of the subjects was 59.5 out of 100, which corresponds to the level requiring “monitoring”. Compared to the 64.4 score of students in the 5th and 6th grades of six metropolitan cities, the scores of the present subjects were lower. The NQ components were 57.4 for balance factors, 52.4 for moderation factors, 55.0 for diversification factors, 57.6 for practice factors, and 80.1 for environmental factors. Regarding the characteristics according to the NQ level, the score (61.5 in 7 times/wk vs. 55.3 in 1-2 or none times/wk) tended to be higher in subjects who frequently eat with their families (p<0.001). In conclusion, nutrition education should be provided to students to increase the frequency of meals with their families, to develop a habit of exercising regularly, and reduce the consumption of ramen, cookies, and processed drinks that are frequently consumed. These results can be used as basic data to develop nutrition education programs to improve the dietary habits and nutritional status of students in Gwangju.